2013
DOI: 10.1093/annonc/mdt280
|View full text |Cite
|
Sign up to set email alerts
|

Family history of cancer and the risk of cancer: a network of case–control studies

Abstract: Our results point to several potential cancer syndromes that appear among close relatives and may indicate the presence of genetic factors influencing multiple cancer sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 29 publications
8
62
0
Order By: Relevance
“…The finding is also consistent with a case-control study in South-east Siberia (Zhivotovskiy et al, 2012), a report that a first degree family history of CRC in those undergoing colonoscopy was associated with the finding of pathologically significant lesions (Castiglione et al, 2012) and the outcome of a study involving a network of 13 case-control studies conducted across various parts of Italy and Switzerland (Turati et al, 2013). With regard to diet, the present study found no statistically significant associations between various dietary intakes and the risk of CRC.…”
Section: Discussionsupporting
confidence: 88%
“…The finding is also consistent with a case-control study in South-east Siberia (Zhivotovskiy et al, 2012), a report that a first degree family history of CRC in those undergoing colonoscopy was associated with the finding of pathologically significant lesions (Castiglione et al, 2012) and the outcome of a study involving a network of 13 case-control studies conducted across various parts of Italy and Switzerland (Turati et al, 2013). With regard to diet, the present study found no statistically significant associations between various dietary intakes and the risk of CRC.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with a case-control study of the The CpG island methylator phenotype (CIMP) status of 3,119 primary populationbased colorectal cancer tumors from the multinational Colon Cancer Family Registry, reported that family history of CRC had decreased risk for CIMP, that represents a subset of colorectal cancer (Weisenberger et al, 2015). However, our result are in contrast with most previous studies which report family history of CRC to increase the risk for CRC (Johns and Houlston, 2001;Zhivotovskiy et al, 2012;Castiglione et al, 2012;Turati et al, 2013;Askling et al, 2001;Stegeman et al, 2013). Indeed, family history of any cancer has been shown to be associated with CRC in the Thai population (Sriamporn et al, 2007;Promthet et al, 2010;Poomphakwaen et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Socioeconomic status is influential in oral cancer (Moles et al, 2008). Many other factors are possibly implicated in mouth, lip and oropharyngeal cancers, including immunosuppression (van Leeuwen et al, 2009), familial and genetic factors (Turati et al, 2013), diet (Garavello et al, 2009), marijuana use (Marks et al, 2014), and even exercise (Nicolotti et al, 2011).…”
Section: Introductionmentioning
confidence: 99%